PENGARUH DEWAN KOMISARIS INDEPENDENSI, KOMITE AUDIT SERTA PROFITABILITAS YANG DISERTAI LEVERAGE DALAM MENGUNGKAPAN LAPORAN SUSTAINABILITY - Hariono, William Christian; Dyah Ayu, Stephana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to examine the impact of the Independent Board of Commissioners, Audit Committee, Profitability, Leverage on the disclosure of the Sustainability Report. This assessment is quantitative and contains secondary data obtained through annual reports or information as well as ongoing information. The population in this study used purposive sampling. The total sample used was 115, covering all companies in all sectors that were verified on the IDX or the Indonesian stock exchange. The data analysis uses media software or the IBM SPSS Statistics 25 application. This study uses multiple linear regression analysis, and the results of the study show that the Independent Board of Commissioners, Audit Committee, Profitability have an impact on the disclosure of the Sustainability Report. However, the Leverage variable has no impact on the disclosure of the Sustainability Report. Keywords: Sustainability Report, Independent Board of Commissioners, Audit Committee, Profitability, Leverage